Structural and Phylogenetic Analysis of Rhodobacter capsulatus NifF: Uncovering General Features of Nitrogen-fixation (nif)-Flavodoxins - Pérez-Dorado, Inmaculada (MDPI, 2013)
Analysis of the crystal structure of NifF from Rhodobacter capsulatus and its homologues reported so far reflects the existence of unique structural features in nif flavodoxins: a leucine at the re face of the isoalloxazine, an eight-residue insertion at the C-terminus of the 50’s loop and a remarkable difference in the electrostatic potential surface with respect to non-nif flavodoxins. A phylogenetic study on 64 sequences from 52 bacterial species revealed four clusters, including different functional prototypes, correlating the previously defined as “short-chain” with the firmicutes flavodoxins and the “long-chain” with gram-negative species. The comparison of Rhodobacter NifF structure with other bacterial flavodoxin prototypes discloses the concurrence of specific features of these functional electron donors to nitrogenase.